Tolerance of the Khojaghand-Nakbandian order of tolerance - Bakhtiyorovich, Dehkonov Bekzod (Universitas Muhammadiyah Sidoarjo, 2019)
This article analyzes the views of Hodgardon-Nakshbandian people on the teachings and attitudes towards tolerance. It also outlines the religious-philosophical and educational aspects of the concept of tolerance.